2016
DOI: 10.1021/acs.joc.6b00778
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Boron-Catalyzed N-Alkylation of Amines with Carboxylic Acids

Abstract: Mechanistic study has been carried out on the B(C6F5)3-catalyzed amine alkylation with carboxylic acid. The reaction includes acid-amine condensation and amide reduction steps. In condensation step, the catalyst-free mechanism is found to be more favorable than the B(C6F5)3-catalyzed mechanism, because the automatic formation of the stable B(C6F5)3-amine complex deactivates the catalyst in the latter case. Meanwhile, the catalyst-free condensation is constituted by nucleophilic attack and the indirect H2O-elim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 106 publications
1
17
0
3
Order By: Relevance
“…Path B includes reduction of the carboxylic acid to the aldehyde and subsequent reductive amination of aldehydes. Very recently, through the use of density functional calculations the group of Yu and Fu proposed that the B(C 6 F 5 ) 3 ‐catalyzed alkylation of N ‐methylaniline with formic acid in the presence of PhSiH 3 (Scheme a) included acid–amine condensation and amide reduction steps (Scheme , path A) . However, this mechanism cannot explain the fact that indole hydrogenation was observed in these experiments.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Path B includes reduction of the carboxylic acid to the aldehyde and subsequent reductive amination of aldehydes. Very recently, through the use of density functional calculations the group of Yu and Fu proposed that the B(C 6 F 5 ) 3 ‐catalyzed alkylation of N ‐methylaniline with formic acid in the presence of PhSiH 3 (Scheme a) included acid–amine condensation and amide reduction steps (Scheme , path A) . However, this mechanism cannot explain the fact that indole hydrogenation was observed in these experiments.…”
Section: Introductionmentioning
confidence: 92%
“…Using density functional calculations, the group of Yu and Fu proposed that the B(C 6 F 5 ) 3 -catalyzed alkylation of N-methylaniline with formica cidi nt he presence of PhSiH 3 included acid-amine condensation and amide reduction steps (Scheme 2). [6] The acid-amine condensation proceeds through ac atalyst-free mechanism, whereas the subsequent amide reduction proceeds by aL ewis acid [B(C 6 F 5 ) 3 ]-catalyzed mechanism. They also performed the acid-amine condensation reaction and obtained the amide in 35 %y ield at 50 8C.…”
Section: Stage Iii:t Wo Sequential Silyl-group and H à à Transfers Tepsmentioning
confidence: 99%
“…In the Lewis acid catalysis (Scheme 6), the Si-H bond of the silane is activated by B(C 6 F 5 ) 3 and then will further react with a silanol to produce the disiloxane with concomitant release of H 2 . By contrast, hydrosilylation reactions catalyzed by B(C 6 F 5 ) 3 are generally characterized by the formation of borane-silane complex (Parks and Piers, 1996;Parks et al, 2000;Rendler and Oestreich, 2008;Sakata and Fujimoto, 2013;Zhang et al, 2016;Cheng et al, 2018). Furthermore, several experimental and theoretical mechanistic studies have suggested that boranecatalyzed reactions of siloxanes are initiated by activation of the silane Si-H bond (Parks et al, 2000;Hog and Oestreich, 2009;Mewald and Oestreich, 2012;Sakata and Fujimoto, 2013;Mathew et al, 2017).…”
Section: Mechanistic Considerationsmentioning
confidence: 99%
“…Control experiments indicated an amide intermediate, and later confirmed by DFT calculations. 67 Surprisingly, the initial condensation with formic acid was a catalyst-free process, followed by two consecutive hydride transfers to produce the N-alkylated amines.…”
Section: Scheme 30 Representative Examples Using Fu and Shang's Condimentioning
confidence: 99%